The Outlandish Companion : Volume Two : in which much more is revealed regarding The fiery cross, A breath of snow and ashes, An echo in the bone and Written in my own heart's blood, and hte world of Outlander, including detailed synopses, maps, medical procedures, chronologies, and highly opinionated essays by the author - Gabaldon, Diana; Porter, Davina; Witherspoon, Pilar; Woodman, Jeff; Recorded Books, LLC. (Prince Frederick, MD : Recorded Books, 2015)
The second volume of a comprehensive companion guide to each book in the "Outlander" series includes a complete chronology of the series, synopses of novels, a guide to research sources, a Scottish glossary and pronunciation guide, and essays by the author.
Title from container.
Compact disc.
In container (17 cm.).
Narrated by the author, with Davina Porter, Pilar Witherspoon, and Jeff Woodman.
Keywords: Gabaldon, Diana; Gabaldon, Diana -- Authorship; Gabaldon, Diana -- Books and reading; Randall, Claire (Fictitious character); Fraser, Jamie (Fictitious character); Time travel in literature; Scotland -- In literature; Audiobooks; Romance fiction; Historical fiction; Fantasy fiction